Analisis Faktor-Faktor yang Mempengaruhi Pemilihan Bank Syariah pada Generasi Z di Kota Surakarta - Siti Saringatul Mangisah; Yuni Astuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the factors that affect the selection of Islamic banks in Generation Z. The research method used is a quantitative method using SmartPLS version 3.0. The population in this study is generation Z in Surakarta City with a questionnaire distributed to 160 respondents. The data analysis method used in the study is the measurement model (outer model), namely the validity test and the Reliability test, the structural model (inner model) includes: the determination coefficient test or R-Square (R2), and the hypothesis test with the t-statistical test. The results of the study show that Product Knowledge has a positive but not significant effect on Generation Z's Interest in Saving, while Facilities and Religiosity have a positive and significant effect on Generation Z's Interest in Saving. In addition, the variable of Product Knowledge needs to be further researched because a deep understanding of Islamic banking products also has the potential to influence the decision of Generation Z in choosing Islamic Banks as a place to save.